Calcium Sets the Clock in Ameloblasts - Said, Raed; Lobanova, Liubov; Papagerakis, Silvana; Papagerakis, Petros (Frontiers in Physiology, 2020)
Background Stromal interaction molecule 1 (STIM1) is one of the main components of the store operated Ca2+ entry (SOCE) signaling pathway. Individuals with mutated STIM1 present severely hypomineralized enamel characterized as amelogenesis imperfecta (AI) but the downstream molecular mechanisms involved remain unclear. Circadian clock signaling plays a key role in regulating the enamel thickness and mineralization, but the effects of STIM1-mediated AI on circadian clock are unknown. Objectives The aim of this study is to examine the potential links between SOCE and the circadian clock during amelogenesis. Methods We have generated mice with ameloblast-specific deletion of Stim1 (Stim1fl/fl/Amelx-iCre+/+, Stim1 cKO) and analyzed circadian gene expression profile in Stim1 cKO compared to control (Stim1fl/fl/Amelx-iCre–/–) using ameloblast micro-dissection and RNA micro-array of 84 circadian genes. Expression level changes were validated by qRT-PCR and immunohistochemistry. Results Stim1 deletion has resulted in significant upregulation of the core circadian activator gene Brain and Muscle Aryl Hydrocarbon Receptor Nuclear Translocation 1 (Bmal1) and downregulation of the circadian inhibitor Period 2 (Per2). Our analyses also revealed that SOCE disruption results in dysregulation of two additional circadian regulators; p38α mitogen-activated protein kinase (MAPK14) and transforming growth factor-beta1 (TGF-β1). Both MAPK14 and TGF-β1 pathways are known to play major roles in enamel secretion and their dysregulation has been previously implicated in the development of AI phenotype. Conclusion These data indicate that disruption of SOCE significantly affects the ameloblasts molecular circadian clock, suggesting that alteration of the circadian clock may be partly involved in the development of STIM1-mediated AI.